Cultural adaptation and validation of the Portuguese End of Life Spiritual Comfort Questionnaire in Palliative Care patients - Pinto, Sara (2016)
Background: Holistic comfort is an important outcome in palliative care and an important goal for patients, relatives and healthcare workers. Holistic comfort considers one’s acceptance of life circum- stances, support from loved ones and health care professionals, and peaceful resolution of relationships during stressful situations. However, this type of comfort is still difficult to measure, particularly in pal- liative care patients, as there is a lack of instruments available, especially in the Portuguese language. This study aims to provide an accurate and sensitive instrument to assess the spiritual comfort of Portuguese palliative care patients. Objective: To perform the cultural adaptation and validation of a Portuguese version of the End of Life Comfort Planning Questionnaire in Palliative Care patients. Methods: Methodological research, with analytical approach. The translation, synthesis, back translation, review, pretest, semantic evaluation and analysis of the psychometric properties were performed. A total of 141 palliative care patients from acute medical-surgical settings at a central hospital in the north of Portugal were recruited. The Ethics Committee approved the research. Results: The internal consistency analysis of the adapted instrument resulted in a global alpha value of 0.84 and the factor analysis presented a solution with five factors with rational meaning. The Portuguese version comprised 20 items. Conclusions: The instrument has good psychometric properties. It was reliable, valid and sensitive to the existence of the spiritual comfort of palliative care patients, and appropriate for further research.